BOOK REVIEW: TRANSLATION CRITICISM ON THE INDONESIAN VERSION OF THE ALCHEMIST BY PAULO COELHO - Isnaeni, Rahmalia (LANTERN (Journal on English Language, Culture and Literature), 2014)
The Alchemist is one of Paulo Coelho’s works. This novel has a different story from other fiction novels. The story is very inspiring about a shepherd who tries to realize the dream he believe in Egypt. The Alchemist has also many wise and meaningful words.Book review that will be presented by the writer in this time is different from the other book reviews. The writer will criticize the translation process that has been done by the translator,Tanti Lemana, in the Indonesian version of The Alchemist. The criticism discuss about the strengths and weaknesses of the translation process, such as; the translation method, the translation errors, the translator awareness of cultural context, and the unfamiliar terms. However, although this book review contains about the writer criticism, but the purpose is not to judge that the translation process done by the translator is good or even bad. The main purpose of this book is simply to know the influence of the translation process toward the Indonesian version of The Alchemist.